Mitochondrial genome complexity in Erodium stephanianum (Geraniaceae): nanopore sequencing reveals chloroplast gene transfer and DNA rearrangements - Xu, Xinchen; Meng, Qingfei; Li, Na; Zou, Zichuan; Yang, Haonan; Li, Ang; Ge, Fusheng; Meng, Jian; Ding, Zixue (Frontiers in Genetics, 2025)
The mitochondrial genome of Erodium stephanianum (Geraniaceae) exhibits remarkable complexity revealed through nanopore sequencing, which has unveiled both chloroplast-to-mitochondrion gene transfer and extensive DNA rearrangements. We collected leaf samples from E. stephanianum in June 2023, subsequently extracting total DNA and sequencing the mitogenome using both Oxford Nanopore and Illumina technologies. The assembly yielded a circular mitochondrial genome of 365,414 base pairs, encompassing 28 unique protein-coding genes, 18 tRNA genes, and 3 rRNA genes. Notably, 55 fragments, totaling 58,305 base pairs, showcased sequence homology between the chloroplast and mitochondrion, indicating substantial gene transfer with implications for evolutionary adaptation. Furthermore, codon usage analysis revealed preferential codon utilization, while microsatellite and repeat sequence analyses identified numerous SSRs and tandem repeats within the mitogenome. Phylogenetic analysis positioned E. stephanianum within the Geraniales order, closely clustering with Geranium maderense. This study highlights the dynamic evolution of mitochondrial genomes in E. stephanianum, emphasizing the significance of interorganellar gene transfer and genome rearrangement.